Study of the practice of homeopathic General Practitioners in France - Trichard, M; Lamure, E; Chaufferin, Gilles (Homeopathy, 2003)
Little is known about the practice of homeopathic general practitioners (GPs) in France. We report a descriptive, cross-sectional study on this subject. The aim was to acquire a clearer idea of (1) the type of patients who consult homeopathic GPs and (2) the type of treatment provided by such GPs, in terms of diagnoses, prescriptions and costs. The survey was carried out on a representative sample of the French homeopathic GP population and covered three seasons of the year. The data was collected by means of a questionnaire which GPs completed for each consulting patient. It emerged that the type of patients who consult homeopathic GPs are chiefly women, between the ages of 20 and 54, living in an urban environment, not in employment, covered by National Health Insurance for Salaried Workers, and belonging to a Mutual Benefit Association. The most common reasons for consultation were ENT disorders, stress and anxiety. The homeopathic GPs mainly used homeopathy to treat these disorders. On average, four medicinal products per patient were prescribed per 2-month course of treatment, for an average reimbursed cost of 3.78€.
Keywords: medical practice; homeopathic GPs; France; patients; medicinal products; diagnoses; costs